Gut-Heart Axis: Microbiome Involvement in Restrictive Cardiomyopathies - Samuel Jaimez-Alvarado; Itzel Ivonn López-Tenorio; Javier Barragán-De los Santos; Dannya Coral Bello-Vega; Francisco Javier Roldán Gómez; Amedeo Amedei; Enrique Alexander Berrios-Bárcenas; María Magdalena Aguirre-García (Biomedicines)
An intriguing aspect of restrictive cardiomyopathies (RCM) is the microbiome role in the natural history of the disease. These cardiomyopathies are often difficult to diagnose and so result in significant morbidity and mortality. The human microbiome, composed of billions of microorganisms, influences various physiological and pathological processes, including cardiovascular health. Studies have shown that gut dysbiosis, an imbalance in the composition of intestinal bacteria, can contribute to systemic inflammation, a key factor in many cardiovascular conditions. An increase in gut permeability, frequently caused by dysbiosis, allows bacterial endotoxins to enter the bloodstream, activating inflammatory pathways that exacerbate cardiac dysfunction. Recent reports highlight the potential role of microbiome in amyloidogenesis, as certain bacteria produce proteins that accelerate the formation of amyloid fibrils. Concurrently, advancements in amyloidosis treatments have sparked renewed hopes, marking a promising era for managing these kinds of diseases. These findings suggest that the gut–heart axis may be a potential factor in the development and progression of cardiovascular disease like RCM, opening new paths for therapeutic intervention. The aim of this review is to provide a detailed overview of the gut–heart axis, focusing on RCM.